Seasonal and long-term changes in habitat selection by Greenland White-fronted Geese Answer albifrons flavirostris in Ireland - Norriss, D W; Wilson, H J (Wildfowl, 1993)
Bogs and other semi-natural wetlands have provided traditional feeding habitats for Greenland White-fronted Geese wintering in Ireland, although many flocks now feed predominantly in farmland. Use of the wettest habitats and arable crops predominates in autumn, most feeding is on various grasslands in winter and on dry grasslands in spring. Habitat loss and disturbance pressures now restrict the range of feeding habitats available to most flocks, resulting in marked interflock variability in habitat use. Shifts to farmland feeding have coincided with beneficial farmland changes rather than with losses of traditional habitats. The implications for the retention of traditional feeding patterns are discussed.